PENGARUH PENGETAHUAN AWAL AKUNTANSI DAN EFIKASI DIRI TERHADAP TINGKAT PEMAHAMAN AKUNTANSI MELALUI MINAT BELAJAR PADA MAHASISWA JURUSAN AKUNTANSI UNIVERSITAS PGRI ADI BUANA SURABAYA - Taufiq, Mohammad (UNIVERSITAS NEGERI SURABAYA, 2015)
This study was conducted to analyze the effect of accounting prior knowledge, self-efficacy, and interest in the level of understanding of accounting majors accounting PGRI Adi Buana University of Surabaya. The approach used in this research is quantitative. Populations are the second semester students 2014/2015 Accounting Department of Economics, PGRI Adi Buana University with a sample of 156 students. Data were analyzed using Structural Equation Modeling (SEM). The results showed that there was a significant effect of prior knowledge of accounting and self efficacy on the interest in learning, and learning interest influencing the level of understanding